Epidemiology of the non-head and neck sebaceous carcinoma and implications for distant metastasis screening - Chen, Xi; Hao, Yangyang; Chou, Mengwei; Yang, Jianqiang (Frontiers in Oncology, 2024)
Introduction: Extraocular sebaceous carcinoma (SC), particularly those outside the head and neck region, are rare and not well-described.Purpose: This study aimed to explore the epidemiology and identify the prognostic factors of non-head and neck SC; describe the possible relevant factors of distant metastasis and provide implications for distant metastasis screening.Methods: Data from the 17 registries of the Surveillance, Epidemiology, and End Results database were retrospectively collected for patients with SC outside the head and neck from 2000 through 2020. Overall survival (OS) and disease specific survival (DSS) were the primary endpoint. Survival analysis was conducted through Kaplan-Meier curves, and multivariate analysis was carried out using Cox proportional hazard models.Results: A total of 1237 patients with SC outside the head and neck were identified.The mean age at diagnosis of the entire patient cohort was 67.7 years (30 to 90+ years), and the mean tumor size was 2.2 cm (0.1-16 cm). Patients with distant disease experienced the lowest OS (mean 29.5 months) than those with localized disease and regional disease (P < 0.0001). Multivariate analysis revealed that age, tumor size, and stage were independent determinants of OS; age, stage, and primary site were independent determinants of DSS. Tumor grade and lymph node status had less prognostic value in survival. Undifferentiated tumors have a trend toward distant metastasis, especially those at the primary site of trunk.The prognosis of the non-head and neck SC is excellent, while the survival of distant disease is very poor. Distant metastasis screening can be considered for undifferentiated tumors, especially those located on the trunk region with large tumor size.